Governing the world : the history of an idea - Mazower, Mark. (New York : The Penguin Press, 2012)
"A history of the project of world government, from the first post-N apoleonic visions of the brotherhood of man to the current crisis of gl obal finance"--
Includes bibliographical references and index.
Keywords: International organization; International cooperation; International relations; World politics